Articulated Ceramic Bricks with Wastes from Ceramic Industries - Viruthagiri1, G.; Nirmala2, G. (Asian Journal of Chemistry, 2013)
Production of ceramic bricks from mixtures of ceramic industry wastes and kaolinitic clay were investigated. Different formulations were prepared to evaluate the effects of each component on drying and firing processes and on the final properties of the ceramic bricks. The samples were investigated mineralogically using FTIR spectra recorded in the region 4000-400 cm-1 and powder X-ray diffraction. The indication of well ordered kaolinite is by the band at 1115 cm-1 in the raw samples which tends to shift towards 1095 cm-1 in all the fired samples. The presence of quartz and anorthite is confirmed both by XRD and FTIR. The samples were analyzed for their mechanical strength up to 50 wt % of the rejects addition before and after sintering (900-1200 ºC). Additions above 40 % decreased the mechanical strength of both the dry body and the fired ceramic pieces.